Flow and heat transfers associated with impinging jets in crossflows - Kabari, L. (Cranfield University, 1977)
This thesis reports the results of an experimental study into the flow and heat transfers associated with both inclined and orthogonally impinging axisymmetric air jets. The majority of previously reported studies have been mainly confined to orthogonally impinging jets in stagnant surroundings. In this investigation, free jets as well as the effects of crossflows are considered. This investigation is Primarily concerned with local heat transfer variations. The experimental tests were. conducted with a single 12.7 mm diameter jet impinging on a flat surface, and heat transfers were evaluated using a heat-mass transfer analogy (t e Chilton-Colburn analogy). The sublimation of naphthalene was employed as the mass transfer technique. The flowfield associated with impinging jets has a significant influence on their heat transfer characteristics., In view of the present limited level of understanding of this 'complex' flowfield, extensive flow visualisation techniques were employed in this present investigation. Those were primarily intended to aid interpretation of the experimental heat transfer results, and also to provide further physical understanding of the flowfields resulting from the interactions between impinging jets and crossflowing streams. The flow and heat transfer tests conducted in the programme of work reported in this thesis covered typical ranges of flow parameters of interest in many practical applications of jet impingement systems. Jet inclinations of 45°, 600, and 90°, nozzle to target spacings of 2,11, and 8 nozzle diameters were studied. The Reynolds nuinbers were 30,200,32,700 and 55,100 and mass velocity ratios In the range 4.0 to 3.8 were studied. The effects of these parameters on the flow and heal transfers associated with impinging jets are reported. Comparisons were drawn between the heat transfer results and those of previously reported studies where appropriate.